The Importance of ICT Adoption in Manufacturing Sector: An Empirical Evidence on SME Business Performance - Nur Yuhainis Ab Wahab; Maliani Mohamad; Yusrinadini Zahirah Yusuff; Rusnifaezah Musa (International Journal of Supply Chain Management, 2020)
Information and communication technologies (ICT) adoption is considered as one of the intangible resources of the organization and needs to be carefully managed to maintain the firm's growth in business performance. Specifically, the objective of this study is to determine the relationship between the ICT adoption and SMEs business performance. According to Resource-based View Theory, technology resources are fundamental drivers to performance. A sample of 155 SMEs data successfully collected through survey. Data collected was analysed using Regression Analysis. The findings revealed that ICT adoption had significant correlation and relationship with business performance of SMEs. The study also suggested that the adoption of ICT is a major factor affecting the SMEs business performance as reported by SME Corporation Malaysia.